Conceptualizing, Measuring, and Explaining Youths' Relative Absence in Legislatures. Issue 2 (10th April 2021) - Sundström, Aksel; Stockemer, Daniel
ABSTRACT: This article conceptualizes the relative absence of youth in legislatures, a feature we perceive as a democratic deficit with detrimental consequences. It introduces a new operationalization: the Youth Representation Index. Rather than calculating youths' representation by the percentage of Members of Parliament 35 or 40 years old and younger or legislatures' median age, we argue that scholars should assess youths' parliamentary presence relative to their proportion of the voting-age population. We contribute by assessing the magnitude of youths' underrepresentation across countries, finding that adults 35 years old and younger are generally underrepresented in legislatures by a factor of three and those 40 years old and younger by a factor of two. We illustrate that youths' presence increases under proportional representation electoral systems and with candidate age requirements set at 18 years. Finally, our results illustrate that countries with a younger population display a stronger discrepancy in youth representation.